Podonomus pepinellii n. sp., first record of the genus and subfamily from Brazil (Diptera: Chironomidae: Podonominae) - Roque, Fabio De Oliveira; Trivinho-Strixino, Susana (Zootaxa, 2004)
The subfamily Podonominae and the genus Podonomus Philippi, 1865, are reported from Brazil for the first time. Podonomus pepinellii n. sp. is described and figured from a single male and associated pupal exuviae.